Identifying English language needs among administrative support staff in a Malaysian Public University: A preliminary study - Mohd Zulfadli Mat Husin; Noor Raha Mohd Radzuan (English Language Teaching Educational Journal, 2021)
English skills particularly in conversation are essential in workplace situations especially in the context of higher learning institutions. Little attention is being given to examining the needs of English communication skills and issues related to administrative support staff at their workplace particularly at public universities. A questionnaire was adopted to gauge the English language needs of support staff, their English skills perception as well as usage at the workplace. Data were collected from a group of 40 support administrative staff from Universiti Malaysia Kelantan (UMK) involving three administrative departments. The findings were gathered using survey and analyzed using content descriptive analysis. The results of the study revealed that the majority of the respondents strongly agreed that having a good English ability will increase their chance of being promoted to a higher position. Data also revealed that staff use English mostly during interaction with foreign staff and students. In addition, staff perceived that they need to improve their English writing skills the most. This study hopes to give better insight towards English proficiency among administrative support staff and explicit policy on English language at workplace. Therefore, English continuous professional development programmes should be developed and introduced to assist in improving their English language abilities.